2018
DOI: 10.1111/imr.12708
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the function, development, and plasticity of type 2 innate lymphoid cells

Abstract: Summary Group 2 innate lymphoid cells (ILC2s) are the most well defined group of ILCs. ILC2 development is controlled by the GATA‐3 transcription factor and these cells produce archetypal type 2 cytokines, such as IL‐5 and IL‐13. These cytokines mediate parasite expulsion and tissue repair, but also contribute to type 2 inflammatory diseases, including allergy, asthma and chronic rhinosinusitis with nasal polyps. In response to tightly regulated local environmental cues ILCs can generate characteristics of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 96 publications
(140 reference statements)
0
62
0
Order By: Relevance
“…Functional plasticity, or the capacity to adopt phenotypes similar to other ILC subsets, provides the potential to fine-tune immune responses to different types of cytokines and enables the rapid adaption when confronted with pathogens (see also ref. 50 ). Several studies have demonstrated this interconversion at least in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Functional plasticity, or the capacity to adopt phenotypes similar to other ILC subsets, provides the potential to fine-tune immune responses to different types of cytokines and enables the rapid adaption when confronted with pathogens (see also ref. 50 ). Several studies have demonstrated this interconversion at least in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Further, several studies have demonstrated signi cant heterogeneity and plasticity of ILCs (reviewed in 61 ). For example, in addition to conventional ILC3s, IL-17 production occurs from other ILC sources including "in ammatory" iILC2s (or ILC2-17 s) induced by IL-25, cysteinyl leukotrienes, and notch signaling 9,10,62 .…”
Section: Discussionmentioning
confidence: 99%
“…ILCs are subdivided into three groups: ILC1, ILC2, and ILC3, based on their cytokine profiles and expression of specific transcription factors, mirroring the classification of CD4 + T helper cell subsets into TH1, TH2, and TH17 cells. Type 2 ILCs (ILC2s) resemble TH2 cells as they require the transcription factor GATA‐3; produce type 2 cytokines IL‐4, IL‐5, IL‐9, and IL‐13; and play important roles in immunity against pathogens and type 2 inflammation (Krabbendam et al , 2018). ILC2s also promote tissue recovery following acute injury in multiple organs, such as lung, intestine, and kidney (Monticelli et al , 2011; Cao et al , 2018).…”
Section: Introductionmentioning
confidence: 99%